DAMPAK KELUARGA BROKEN HOME PADA PSIKOLOGIS ANAK DI PANTI ASUHAN MARDHATILLAH PARIAMAN - Rahmi Anggun Pratiwi; Alfi Rahmi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to determine the impact of full day school on student learning concentration at SMA Negeri 4 Pariaman. This type of research is descriptive qualitative research where researchers use observation and interview methods. It appears that students are not effective in adjusting themselves to extra hours throughout the day. One of them is the lack of school during the day, students are very tired. Schools that carry out full day school programs have an impact on students, namely physical exhaustion, mental fatigue, and emotional exhaustion. Students also feel bored and bored, bored in learning and arise boredom and fatigue resulting in a lack of student learning concentration during the learning process. Students who usually go to school in the afternoon now go home in the afternoon, plus the assignments or homework given by the subject teacher are too excessive, this has an impact on students being unable to concentrate and forget easily. At the beginning of the full day school program at school, many students complained, were tired, several weeks of full day school, many students did not attend due to illness and some were absent without explanation, each class must have been absent every day, more than five people . So the conclusion is that full day school has an impact on student learning concentration at SMA Negeri 4 Pariaman.